Epidemiology of Bovine Tuberculosis and Its Zoonotic Implication in Addis Ababa Milkshed, Central Ethiopia - Tulu, Begna; Zewede, Aboma; Belay, Mulugeta; Zeleke, Miserach; Girma, Mussie; Tegegn, Metasebia; Ibrahim, Fozia; Jolliffe, David A.; Abebe, Markos; Balcha, Taye Tolera; Gumi, Balako; Martineau, Henny M.; et al. (Frontiers in Veterinary Science, 2021)
Bovine tuberculosis (bTB) continues to be one of the most widely distributed chronic infectious diseases of zoonotic importance, which causes a significant economic loss in animal production. A cross-sectional study was conducted to estimate the prevalence of bTB, its associated risk factors, and type the M. bovis isolated in central Ethiopia. A total of 65 dairy farms and 654 cattle were tested for bTB using a single intradermal cervical comparative tuberculin test (SCCIT) test. Data on farm management, animal-related characteristics, and the owner’s knowledge of the zoonotic importance of bTB were collected using a structured questionnaire. In addition, a total of 16 animals from different farms were identified for post mortem examination. Lowenstein Jensen (LJ) culture was also conducted and spoligotyping was used to type the M. bovis strains isolated. Chi-square test and logistic regression models were used to analyze the herd and animal level risk factors. Herd level and animal level prevalence of bTB were 58.5% (95% CI: 46.2-69.2%) and 39.3% (95% CI: 35.5-43.5%), respectively. At the herd level, poor farm management was the predictor for bTB positivity (p<0.05). Animal breed, poor body condition score, farm type, and poor farm management conditions were significant predictors of bTB positivity (p< 0.05) at an individual animal level. All animals identified for postmortem examination were found to have gross TB like lesions. A total of 14 M. bovis strains were identified from 12 animals which were positive for LJ culture. The strain with the largest number of clusters (5 isolates) was SB1176, followed by SB0134 (3 isolates), SB0192 (2 isolates), and SB2233 (2 isolates), and 2 new strains, each consisting of only one isolate. The majority (58.5%) of the respondents did not know the zoonotic importance of bTB. The result of this study showed a high prevalence of bTB in the Addis Ababa milkshed and a low level of consciousness of the owners on its transmission to humans. Therefore, the launching of acceptable control measures of bTB and the creation of public awareness about its zoonotic transmission and prevention measures are required.